PERTUMBUHAN INSTITUSI PENDIDIKAN AWAL DI INDONESIA - Saiful Bahri (Pascasarjana UIN Sumatera Utara, 2021)
Islamic educational institutions are a sub-system of the community or nation system. Therefore, in its operations, it always refers to and is responsive to the needs and developments of the community. Thus, Islamic educational institutions must be organized by the demands and aspirations of the community because without this. It will be difficult to achieve progress and development in Islamic education in Indonesia. From various previous explanations about early institutions in Indonesia, as a first step, they have contributed significantly to the development of Islamic education among Indonesian Muslims. Among several Islamic educational institutions, mosques, meunasah, dayah, pesantren, surau and finally madrasas have emerged, which have a significant role and continue to experience development and progress with their respective characteristics until now. However, the current function has changed significantly because of the changing and dynamic conditions.